Balance sectorial utilizando modelos matemáticos: Aplicación en Cuba - Roberto René Moreno García; Katia María Parra Pérez; Rodolfo Roberto Moreno Parra; Ulises Pacheco Feria; José Daniel Nieto Columbié; Víctor Salvador Soulary Carracedo; Laura Piedra Mu\~noz; Emilio Galdeano-Gómez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– The objective of the paper is to equilibrate the sectorial imbalances of the production of goods and services, identified in the Cuban productive structure, following a methodology that includes mathematical modeling. Econometric and goal programming (GP) models are designed to assess the relative importance, to estimate and to solve the imbalances between the intermediate and final destination in economic sectors of the Cuban economy. This makes it possible to design public policies focused on improving economic complementarity and integration, a relevant aspect in the process of updating the Cuban economic and social model, endorsed in the government documents governing the economic reform undertaken since 2011. As a result, the methodology is applied in the province of Santiago de Cuba, where sectorial imbalances were estimated and productive capacities reserves of goods and services by 42.500 million pesos were identified to equilibrate the imbalances, which can contribute to investment decision-making within the framework of the country's economic and social development strategy until 2030.
Keywords: C01; C02; D58; E22; 330; sectorial balance; econometric; goal programming